ON LOGICAL CHARACTERISATION OF HUMAN CONCEPT LEARNING BASED ON TERMINOLOGICAL SYSTEMS. - Badie, Farshad (Logic & Logical Philosophy, 2018)
The central focus of this article is the epistemological assumption that knowledge could be generated based on human beings' experiences and over their conceptions of the world. Logical characterisation of human inductive learning over their produced conceptions within terminological systems and providing a logical background for theorising over the Human Concept Learning Problem (HCLP) in terminological systems are the main contributions of this research. In order to make a linkage between 'Logic' and 'Cognition', Description Logics (DLs) will be employed to provide a logical description and analysis of actual human inductive reasoning (and learning). This research connects with the topics 'logic & learning', 'cognitive modelling', and 'terminological knowledge representation'.